Something s growing in those cities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Seminar 'Growing Cities, Growing Food Urban Agriculture on the Policy Agenda', held in Havana, Cuba, in October 1999